Malaysian accounting teachers’ preferences and practices towards assessment - Arumugham, Kalai Selvan; Shaik Abdullah, Sarimah; Mahmud, Nafisah (2016)
Past studies have reported differently on teachers’ assessment preferences: Some documenting preferences for the traditional pen and paper examination while others reporting preferences for school-based assessment. The Malaysian Examination Syndicate has introduced a mix of both assessment approaches in accounting education with the aim to improve overall student learning. This qualitative study explores ten Malaysian secondary school accounting teachers’ assessment preferences, the reasons for their choices and how their preferences were translated into practice. Findings from semi-structured interviews and document analysis revealed a complex interplay of teachers’ preferences and their teaching practices due to various contextual factors.